Total air temperature anomalies as a metric for detecting high-altitude ice crystal events: Development of a failure indicator heuristic. (November 2019) - Rodríguez-Sanz, Álvaro; Arnaldo Valdés, Rosa; Gómez Comendador, Fernando; Sánchez Ayra, Eduardo; Cano Cancela, Javier
Abstract: High-Altitude Ice Crystals (HAIC) constitute a hazard to commercial aircraft flying near deep convective weather due to jet-engine power loss and air data probes malfunction. HAIC can stick to warm metal surfaces in jet-engines and cause engine surge, stall, flameout and rollback, power loss, as well as engine compressor damage due to ice shedding. Along with these events, disruption to aircraft systems are noted when HAIC are ingested into air data probes (Pitot tube and/or Total Air Temperature -TAT- sensor), causing erroneous measurements of temperature and air speed. Particularly, the TAT probe incorrectly reporting zero degrees Celsius or in error is known to be evidence of ice crystals in the atmosphere surrounding the aircraft. These TAT anomalies are due to the accumulation of ice crystals in the TAT sensor, producing a zero degrees Celsius reading, generating failures in airspeed indicators and acting as potential incident/accident precursors. In this paper, TAT events from pilot reports and Flight Data Monitoring (FDM) are analyzed. TAT FDM data analysis covers two types of engines, which are used on short, medium and long-range routes. The study includes eight aircraft fleet types. Based on these analyses, we present a sensor-failure-tolerant heuristic that generates a reliability indicator, founded on the differences between the TAT and the engine's inlet temperature sensors. It aims to provide early warnings to pilots regarding HAIC events and prevent potential data errors and system failures. Highlights: High-Altitude Ice Crystals (HAIC) can obstruct aircraft pitot probes during the cruise phase. Total Air Temperature (TAT) probe anomalies are evidence of ice crystals in the atmosphere. TAT events from pilot reports and Flight Data Monitoring are analyzed. We present different heuristics that generates reliability indicators regarding TAT events. Routes flying through the Inter-Tropical Convergence Zone are more likely to experience TAT events.